INOVASI TELUR ITIK ASIN: STUDI KOMBINASI JERUK PURUT (Citrus hystrix) DAN CABE RAWIT (Capsicum frutescens) TERHADAP MUTU ORGANOLEPTIK - Riskayanti Riskayanti; Firdaus Husein; Lailatun Nisfimawardah; Monasdir Monasdir (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
This study aims to evaluate the organoleptic quality of salted duck eggs treated with a combination of lime leaves (Citrus hystrix) and cayenne pepper (Capsicum frutescens), and to determine the best formulation that produces optimal organoleptic quality. The study was conducted using the completely randomized design (CRD) method, consisting of 4 treatments and 6 replicates, each of which included 3 duck eggs, with treatment P0: without lime (Citrus hystrix) with cayenne pepper (Capsicum frutescens), P1: 20% lime (Citrus hystrix) + 80% cayenne pepper (Capsicum frutescens), P2: 50% lime (Citrus hystrix) + 50% cayenne pepper (Capsicum frutescens), P3: 80 kaffir lime (Citrus hystrix) + 20% cayenne pepper (Capsicum frutescens). The results of the Analysis of Variance (ANOVA) showed a significant effect (P<0.05) on aroma and taste, but color, texture, and preference level did not show a significant effect (P<0.05). Consumers most preferred salted duck eggs combined with a mixture of 20% kaffir lime (Citrus hystrix) and 80% cayenne pepper (Capsicum futescens) extract (P1), while the least preferred salted duck eggs were those containing 80% kaffir lime (Citrus hystrix) and 20% cayenne pepper (Capsicum futescens) extract (P3).